(untitled) (Modern American Journal of Medical and Health Sciences, 2025)
The visual arts have played a crucial role in human civilization, evolving over the centuries to reflect changing cultural, social, and technological landscapes. The three articles cover the history of visual art production from modern civilizations to the present day. It explores the importance of visual art in modern society, and the editorial emphasizes its role in fostering creativity, cultural communication, and the expression of emotions.